Amplifying children's voices within photovoice: Emerging inclusive education practices in Indonesia. - Bonati, Michelle L.; Andriana, Elga (British Journal of Learning Disabilities, 2021)
Accessible summary: Inclusive education is being developed for the first time in Indonesia.Children with learning disabilities have been excluded from regular schools in the past, but now some schools are welcoming these students.Supporting social inclusion is important for students with learning disabilities who have been excluded from participating in school and their communities.This article talks about how a research method called photovoice can be used to support social inclusion in school.This article shows how photovoice can be used to understand how students with learning disabilities think and feel about social inclusion, their communities and belonging. Background: Inclusive education is a recent phenomenon in Indonesia. Students with learning disabilities have been historically and currently marginalised within most schools and communities, with limited opportunities for social inclusion. Methods: Photovoice, a qualitative, participatory methodology was implemented to engage 31 students with learning disabilities and without disabilities in projects connected with their school curricula that focused on the overarching themes of social inclusion, belonging and community. The students served as co‐researchers, which involved taking photographs and thematically analysing them during individual interviews and during group discussions. The project culminated with a public photo exhibition and presentations by the students. Data collection occurred over 6 weeks, in two schools in Yogyakarta, Indonesia, and further cross‐case analysis of the data was conducted by the authors. The research question examined was as follows: How do students with and without disabilities perceive social inclusion, belonging and their community during a photovoice project in Indonesia? Findings: Three themes emerged in response to the research question focused on the overarching topics of social inclusion, belonging and community. These themes included: (1) Inclusive Characters, (2) Cultural and Civic Engagement in the Community, and (3) Self‐Determination. Conclusions: Photovoice methodology can provide a pedagogical tool within inclusive education practices. Photovoice also provided opportunities to amplify the voices of students with learning disabilities to express their experiences and perspectives of social inclusion in their schools and communities. Students with and without disabilities also developed a sense of agency to transform the communities in which they belong.